Mitochondria, energy, and metabolism in neuronal health and disease - Trigo, Diogo; Avelar, Catarina; Fernandes, Miguel; Sá, Juliana; Cruz e Silva, Odete (FEBS letters, 2022)
Mitochondria are associated with various cellular activities critical to homeostasis, particularly in the nervous system. The plastic architecture of the mitochondrial network and its dynamic structure play crucial roles in ensuring that varying energetic demands are rapidly met to maintain neuronal and axonal energy homeostasis. Recent evidence associates aging and neurodegeneration with anomalous neuronal metabolism as age‐dependent alterations of neuronal metabolism are now believed to occur prior to neurodegeneration. The brain has a high energy demand, which makes it particularly sensitive to mitochondrial dysfunction. Distinct cellular events causing oxidative stress or disruption of metabolism and mitochondrial homeostasis can trigger a neuropathology. This review explores the bioenergetic hypothesis for the neurodegenerative pathomechanisms, discussing factors leading to age‐related brain hypometabolism and its contribution to cognitive decline. Recent research on the mitochondrial network in healthy nervous system cells, its response to stress, and how it is affected by pathology, as well as current contributions to novel therapeutic approaches will be highlighted. This review discusses the hypothesis that hypometabolism and mitochondrial dysfunction in neuronal cells represent pathogenic events triggering cognitive decline and neurodegenerative diseases.